The roots of digital aggression: Exploring cyber-violence through a systematic literature review - Muaadh Mukred; Umi Asma' Mokhtar; Fahad Abdullah Moafa; Abdu Gumaei; Ali Safaa Sadiq; Abdulaleem Al-Othmani (International Journal of Information Management Data Insights)
In both the developed and developing world, cyber-violence presents a problem that affects most families and societies. However, there is a lack of diagnostic studies dedicated to this phenomenon, especially its factors and the relevant models. Consequently, the aim of this study was to extract the factors that bear upon cyber-violence by conducting a systematic literature review. This was anticipated to lead to a better understanding of those factors with their models and effects, as explored in previous research. This systematic literature review resulted in a comprehensive and rigorous examination of the relevant literature, which included numerous articles of interest. The findings indicate that most of the past research on cyber-violence has primarily looked at the factors affecting the behavioral intention to engage in the phenomenon, while very few studies have looked at its effects, especially in developing countries. The period from which the primary studies were collected was 2010-2024, using the ScienceDirect, IEEE Explorer, Springer, SAGE, Taylor and Francis, MDPI and Emerald Insight databases. Inclusion and exclusion criteria were applied, resulting in 91 studies to be systematically reviewed. It emerged from this review that engagement in cyber-violence was predominantly due to a lack of cyber-violence models and a failure to consider the factors that potentially contribute to engagement in cyber-violence. Hence, these factors are identified in this paper, looking at the academic, economic and social impact of cyber-violence. The outcomes of this review could assist future researchers by providing a roadmap of institutional repositories and guidelines for recognizing the models and factors of cyber-violence, together with its effects.